Saccharomyces cerevisiae SSB1 protein and its relationship to nucleolar RNA-binding proteins. - Jong, A Y (1987)
To better define the function of Saccharomyces cerevisiae SSB1, an abundant single-stranded nucleic acid-binding protein, we determined the nucleotide sequence of the SSB1 gene and compared it with those of other proteins of known function. The amino acid sequence contains 293 amino acid residues and has an Mr of 32,853. There are several stretches of sequence characteristic of other eucaryotic single-stranded nucleic acid-binding proteins. At the amino terminus, residues 39 to 54 are highly homologous to a peptide in calf thymus UP1 and UP2 and a human heterogeneous nuclear ribonucleoprotein. Residues 125 to 162 constitute a fivefold tandem repeat of the sequence RGGFRG, the composition of which suggests a nucleic acid-binding site. Near the C terminus, residues 233 to 245 are homologous to several RNA-binding proteins. Of 18 C-terminal residues, 10 are acidic, a characteristic of the procaryotic single-stranded DNA-binding proteins and eucaryotic DNA- and RNA-binding proteins. In addition, examination of the subcellular distribution of SSB1 by immunofluorescence microscopy indicated that SSB1 is a nuclear protein, predominantly located in the nucleolus. Sequence homologies and the nucleolar localization make it likely that SSB1 functions in RNA metabolism in vivo, although an additional role in DNA metabolism cannot be excluded.